Case report: Overlapping syndrome of MOG-IgG associated optic neuritis and autoimmune encephalitis with co-existence of anti-NMDAR and anti-GABABR antibodies - Mei, Zhujun; Wang, Jingguo; Wang, Junling; Liu, Xiaoni; Deng, Bo; Yang, Wenbo; Zhang, Xiang; Chen, Xiangjun; Yu, Hai (Frontiers in Immunology, 2025)
We report a case of optic neuritis (ON) secondary to autoimmune encephalitis (AE) in a patient with concomitant antibodies to N-methyl-D-aspartate receptor (NMDAR), gamma-aminobutyric acid-B receptor (GABABR), and myelin oligodendrocyte glycoprotein (MOG). The patient exhibited a constellation of symptoms, including vision loss, seizures, mental and behavioral disorders, cognitive impairment, and speech abnormalities. At the two-year follow-up, the patient’s symptoms had abated entirely. Overlap syndrome of triple autoimmune antibodies is rare and the coexistence of antibodies to NMDAR, GABABR and MOG has not been reported till now. This case report provides novel experience of diagnosis and treatment in autoimmune overlap syndromes.